Body dysmorphic disorder in children and young people. (11th February 2021) - Watson, Chloe; Ban, Sasha
Abstract : The incidence of body dysmorphic disorder (BDD) in young people is increasing. Causes of BDD are related to the prevalence of social media and adolescent development, especially the role that brain neuroplasticity has on influencing perception. There are long-term impacts of BDD, including depression and suicide. Prevention and promotion of positive body image are part of the nurse's role; treatment can prevent unnecessary aesthetic surgical interventions.